2020
DOI: 10.1093/biolinnean/blaa163
|View full text |Cite
|
Sign up to set email alerts
|

Eye size in North American watersnakes (genusNerodia) correlates with variation in feeding ecology

Abstract: Visual acuity and sensitivity positively correlate to eye size in vertebrates, and eye size relates to the ecology of colubrid snakes. We investigated whether eye morphology of North American colubrids of the genus Nerodia correlates with ecology as well. Although all members of the genus utilize aquatic habits, they differ widely in the proportion of anurans they eat. We specifically tested whether eye size and placement is associated with the proportion of frogs in the diet to determine whether these two asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
1
0
Order By: Relevance
“…This suggested that the intensity and the propagation of lights provided by different environments can drive the evolution of snake eyes. In the watersnakes that heavily live on frogs, it has been found that the eye size was positively associated with the proportion of frogs in the diet, suggesting that larger eyes benefited the foraging ability of the snakes (Camp et al, 2020). Given the importance of vision in the foraging behavior of snakes, understanding the evolution of snake eyes can thus provide us deeper insights into the diversification of eye morphology and its role in regulating predator-prey interactions across different environmental gradients.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that the intensity and the propagation of lights provided by different environments can drive the evolution of snake eyes. In the watersnakes that heavily live on frogs, it has been found that the eye size was positively associated with the proportion of frogs in the diet, suggesting that larger eyes benefited the foraging ability of the snakes (Camp et al, 2020). Given the importance of vision in the foraging behavior of snakes, understanding the evolution of snake eyes can thus provide us deeper insights into the diversification of eye morphology and its role in regulating predator-prey interactions across different environmental gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, larger animals tend to have relatively smaller eyes than those of smaller animals [2][3][4]. Differences in eye size across the species affect ecological and behavioral factors, such as activity patterns [3], habitats [5], and feeding strategies [6]. It is also known that the growth of eyes and body size is partially faster during ontogenetic development.…”
Section: Introductionmentioning
confidence: 99%